2021
DOI: 10.3126/njb.v9i1.38644
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram and Phytochemical Analysis of Cinnamon, Clove, and Sichuan Pepper Extracts

Abstract: A wide range of medicinal plant extracts has phytochemicals that possess antimicrobial properties and these plants are used to treat several infections. The study aimed to assess the antimicrobial activities of some spices extracts and to evaluate the phytochemicals present in them. The extracts of spices were prepared using Soxhlet apparatus refluxing with methanol and ethanol. The well diffusion technique was implemented for the evaluation of antimicrobial activities of the extracts and the zone of inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The phytoconstituents found were eugenol, gallic acid, chlorogenic acid, quercetin and ursolic acid. Our findings are in agreement with those of Adhikari et al 27 , who reported that the methanol extract of clove had the greatest inhibitory effect on Proteus mirabilis , Pseudomonas aeruginosa and Candida albicans due to the presence of phytochemicals such as flavonoids, polyphenols and tannins. Using gas chromatography‒mass spectrometry (GC‒MS) analysis of clove oil, Ayoola et al 50 reported that the phytoconstituents in clove were caryophyllene, eugenol, eugenol acetate and alpha-humelene, with eugenol being the leading phytoconstituent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The phytoconstituents found were eugenol, gallic acid, chlorogenic acid, quercetin and ursolic acid. Our findings are in agreement with those of Adhikari et al 27 , who reported that the methanol extract of clove had the greatest inhibitory effect on Proteus mirabilis , Pseudomonas aeruginosa and Candida albicans due to the presence of phytochemicals such as flavonoids, polyphenols and tannins. Using gas chromatography‒mass spectrometry (GC‒MS) analysis of clove oil, Ayoola et al 50 reported that the phytoconstituents in clove were caryophyllene, eugenol, eugenol acetate and alpha-humelene, with eugenol being the leading phytoconstituent.…”
Section: Discussionsupporting
confidence: 93%
“…26 , who reported 100% inhibition of the mycelial growth and conidial germination of Curvularia lunata and Fusarium sacchari using bud extracts of S. aromaticum at concentrations of 1000 ppm, 5000 ppm and 10,000 ppm. Adhikari et al 27 reported that methanol S. aromaticum extract was more effective than gentamycin against Pseudomonas aeruginosa, thus corroborating the present findings . The antimicrobial and antifungal effects of S. aromaticum extracts can be attributed to the presence of phenolic compounds, flavonoids, hydroxybenzoic acids and hydroxyphenyl propenes 28 .…”
Section: Discussionsupporting
confidence: 91%
“…Gram-(−) and Gram-(+) strains were used to broaden the possible spectrum of action of the molecules. This type of assay provides information not only on the antibacterial capabilities of the adducts but also allows us to understand which structural changes demonstrate better structure–activity results [ 80 ]. It was carried out primarily to analyze the susceptibility of the probiotic and pathogenic strains to the compounds tested.…”
Section: Methodsmentioning
confidence: 99%
“…Plant extracts can be utilized alone or in combination with other extracts, requiring minimal processing, to achieve synergistic effects in meat and meat products. Recent studies have demonstrated that clove and cinnamon oils ( Adhikari et al, 2021 ; Feng et al, 2022 ), thyme and balsam oils ( Fratianni et al, 2010 ; Altınterim and Kocabaş, 2017 ), as well as hops extracts ( Kramer et al, 2015 ; Arruda et al, 2021 ) exhibit excellent inhibitory effects against meat spoilage bacteria. Plant extracts are generally recognized as safe ( GRAS ) and are preferred by most consumers over synthetic preservatives.…”
Section: Development Of Functional Fermented Poultry Meat Productsmentioning
confidence: 99%